The Role of Academic Supervision in Promoting Teacher Professionalism - Dendi Fitriansyah; Nur Aisyah (Innovative Journal of Educational Research and Insights, 2026)
This study examines the role of academic supervision in promoting teacher professionalism within school settings. Using a qualitative research design, the study explores how supervision practices contribute to improving teachers’ pedagogical competence, instructional performance, and professional development. Data were collected through in-depth interviews, classroom observations, and document analysis involving school principals and teachers as key participants. The findings reveal that academic supervision plays a significant role in enhancing lesson planning, classroom management, and reflective teaching practices. Teachers reported that constructive feedback and collaborative discussions during supervision helped them identify strengths and areas for improvement, leading to more effective teaching strategies. However, the study also identifies several challenges in the implementation of academic supervision, including time constraints, varying levels of supervisor competence, and the perception of supervision as evaluative rather than developmental. Despite these limitations, when conducted systematically and supportively, academic supervision fosters teacher motivation, confidence, and continuous professional growth. The study concludes that effective academic supervision requires a collaborative approach, well-structured planning, and active teacher engagement to maximize its impact on teacher professionalism. These findings provide important implications for improving supervision practices and enhancing the overall quality of education.